Protective effect of ginsenoside Re on damaged cells irradiated by UVC - Zhang, H.; Wang, E.; Chen, X.; Tang, Y.; Wang, H.; Wang, Xuan-Ce; Xu, X. (2013)
Objective: To investigate the protective effects of ginsenoside Re on human embryonic fibroblast RSa cells damaged by ultraviolet C(UVC), and to discuss the anti-UVC mechanism of ginsenoside Re. Methods: The RSa cells were irradiated with different dosages of UVC, and the RSa cells were treated with 50 mg·L -1 ginsenosides before and after irradiation(UVC+Re group), at the same time, UVC model group and UVC+Rg1 group were established. MTT assay was used to analyze the survival rate of cells; apoptosis and cell cycle were measured by flow cytometry (FCM) method, and the activity of superoxide dismutase (SOD) was determined by enzyme biochemical methods. The survival rate of cells after treated with SOD inhibitor was detected by colony formation assay. Results The results of MTT assay showed that the survival rate of the cells in UVC+ Re group and UVC+ Rg1 group were significantly increased compared with UVC model group(P < 0.01 or P < 0.05). The FCM results showed that different dosages of UVC could induce early apoptosis of the RSa cells. The apoptotic rate of cells in UVC+Re group was significantly decreased compared with UVC model group. The cell cycle detection results showed that the percentage of the RSa cells at G 2 phase was significantly increased after UVC irradiation (P < 0.01), and the percentage of the Rsa cells at G 2 phase in UVC+ Re group was significantly decreased compared with UVC model group(P < 0.01), and the ratio of the RSa cells at G 2 phase in UVC+Re group was significantly decreased. Compared with UVC model group, the activity of SOD in UVC+ Re group was incresed (P < 0.01). Conclusion: Ginsenoside Re has anti-UVC efficiency and can enhance the survival rate of RSa cells, and inhibit early apoptosis and increase the SOD activity.